Description of breast diseases of adolescent girls applied to breast office polyclinics - E. A. Sukhareva; L. A. Ponomareva (Опухоли женской репродуктивной системы)
Maintaining of the children and adolescents’ health is a priority tend in health policy of the Russian Federation. Among the total number of women seeking to mammologist clinic health from 2007 to 2011, teenage girls were just 0.3 %. But all of them were found breast disease such as a diffuse form of fibrocystic disease (61 %), nodular breast after surgery (17.3 %), contusion of breast cancer (13 %), non-lactational mastitis (8.7 %). Questionnaire of the adolescents showed that they do not know anything about risk factors of breast diseases, do not conduct monthly self-examination. A set of preventive measures is required to preserve women's reproductive health since their childhood.